Business social responsibility of micro-entrepreneurs - Ragos, Anna Rowena Chua; Chua, Consuelo T. (2008.)
This study compared micro-entrepreneurs with and without business education background in terms of their knowledge of, willingness to, and actual practice of business social responsibility. Their reasons for compliance and non-compliance with business social responsibility.l Their reasons for compliance and non-compliance with business social responsibility were also determined. A sample of 20 micro-entrepreneurs, 10 with business education background and 10 without were chose using snowball sampling. A true or false type test was used to measure the respondent's knowledge on business social responsibility. On the other hand, Likert-type self-administered questionnaires were used to determine willingness and actual practice. Data on the knowledge of and willingness to practice business social responsibility were analyzed using descriptive statistics. Further tests to determine differences on micro-entrepreneurs' knowledge and actual practice depending on their business education were done using Fischer Exact Test for Significance and the Wilcoxon Mann Whitney U Test. Results show that there is no difference in the knowledge of, willingness to, and actual practice of micro-entrepreneurs in terms of their business education background. Overall, respondents are most knowledgeable on aspects of fair labor practices and are least knowledgeable on anti-trust laws. Furthermore, all respondents are willing to practice business social responsibility. The most common business social responsibility practiced pertains to employee protection; while the least applied are practices relating to involvement to government, environment, and consumer protection. The primary reason for complying with business social responsibility is to avoid negative consequences like loss of customers and sales. Other reasons include their personal belief in the importance of business social responsibility, the contribution of social responsibility to improving business performance, and the need to comply with social responsibility expectations. On the other hand, reasons given for non-compliance include lack of financial resources, indifference and ignorance about business social responsibility and mistrust in government agencies. Recommendations for future researchers are provided at the end of the paper.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Small business enterprises -- Philippines; Social responsibility in business -- Philippines